2004
DOI: 10.1023/b:gerg.0000010486.58026.4f
|View full text |Cite
|
Sign up to set email alerts
|

Time Delay in Black Hole Gravitational Lensing as a Distance Estimator

Abstract: We calculate the time delay between different relativistic images formed by black hole gravitational lensing in the strong field limit. For spherically symmetric black holes, it turns out that the time delay between the first two images is proportional to the minimum impact angle. Their ratio gives a very interesting and precise measure of the distance of the black hole. Moreover, using also the separation between the images and their luminosity ratio, it is possible to extract the mass of the black hole. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
172
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(178 citation statements)
references
References 19 publications
6
172
0
Order By: Relevance
“…Schwarzschild black hole time delay between successive relativistic ER then becomes roughly 2π × 3 √ 3M and for JNW it becomes 2π × 1+2ν with previously studied examples for relativistic time delay in the literature which, to the best of our knowledge, have all been either black holes or WNS [6,27,37]. We have confirmed that there are important differences between SNS and WNS for time delays between relativistic images which we discuss below.…”
Section: Time Delaysupporting
confidence: 85%
See 3 more Smart Citations
“…Schwarzschild black hole time delay between successive relativistic ER then becomes roughly 2π × 3 √ 3M and for JNW it becomes 2π × 1+2ν with previously studied examples for relativistic time delay in the literature which, to the best of our knowledge, have all been either black holes or WNS [6,27,37]. We have confirmed that there are important differences between SNS and WNS for time delays between relativistic images which we discuss below.…”
Section: Time Delaysupporting
confidence: 85%
“…The last two solutions have been shown to be obtainable as collapse end states [23,28]. Time delay between relativistic images have previously been studied for Schwarzschild black hole in [6] and in general for spacetimes with photons spheres in [27] (which includes black holes and Weakly Naked Singularities, as we will see later). The present study complements these by computing time delay between relativistic images for Strongly Naked Singularities, ie., naked singularities not covered by photon sphere.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…The measurement of time delay provides a probe of the Hubble constant [3,21]. The general approximative expressions of time delay between relativistic images in strong field limits for asymptotic flat spacetime without a cosmological horizon has been presented in [22].…”
Section: Introductionmentioning
confidence: 99%